Potential applications of glucosyltransferases in terpene glucoside production: impacts on the use of aroma and fragrance - Schwab, Wilfried; Fischer, Thilo C.; Giri, Ashok; Wuest, Matthias (Applied Microbiology and Biotechnology, 2015)
The detection of glucoconjugated forms of monoterpene alcohols in rose petals in the late 1960s opened the new field of nonvolatile aroma precursors in flavor research. It is now well established that odorless glycosides represent a significant pool of aroma precursors in plants where they act as preformed but inactivated defense or attractive chemicals. Technical improvements in the separation and identification of plant secondary metabolites have provided a multitude of chemical structures, but functional characterization of glycosyltransferases that catalyze their formation lags behind. As technical efforts and costs for DNA sequencing dramatically dropped during the last decade, the number of plant genome sequences increased significantly, thus providing opportunities to functionally characterize the glycosyltransferase gene families in plants. These studies yielded the first glycosyltransferase genes that encode efficient biocatalysts for the production of monoterpene glucosides. They have applications in the food, feed, chemical, cosmetic, and pharmaceutical industries as slow release aroma chemicals.

Glucosylation of smoke-derived volatiles in grapevine (vitis vinifera) is catalyzed by a promiscuous resveratrol/guaiacol glucosyltransferase - Haratl, Katja; Huang, Fong-Chin; Giri, Ashok P.; Franz-Oberdorf, Katrin; Frotscher, Johanna; Shao, Yang; Hoffmann, Thomas; Schwab, Wilfried (Journal of Agricultural and Food Chemistry, 2017)
Vinification of grapes (Vitis vinifera) exposed to forest fire smoke can yield unpalatable wine due to the presence of taint compounds from smoke and the release of smoke derived volatiles from their respective glycosides during the fermentation process or in-mouth during consumption. To identify glycosyltransferases (GTs) involved in the formation of glycosidically bound smoke-derived volatiles we performed gene expression analysis of candidate GTs in different grapevine tissues. Second, substrates derived from bushfire smoke or naturally occurring in grapes were screened with the candidate recombinant GTs. A resveratrol GT (UGT72B27) gene, highly expressed in grapevine leaves and berries was identified to be responsible for the production of the phenolic glucosides. UGT72B27 converted the stilbene trans-resveratrol mainly to the 3-O-glucoside. Kinetic analyses yielded specificity constants (k(cat)/K-m) of 114, 17, 9, 8, and 2 mM(-1) s(-1) for guaiacol, trans-resveratrol, syringol, methylsyringol, and methylguaiacol, respectively. This knowledge will help to design strategies for managing the risk of producing smoke-affected wines.

Semirational design and engineering of grapevine glucosyltransferases for enhanced activity and modified product selectivity - Joshi, Rakesh; Trinkl, Johanna; Haugeneder, Annika; Haertl, Katja; Franz-Oberdorf, Katrin; Giri, Ashok; Hoffmann, Thomas; Schwab, Wilfried (Glycobiology, 2019)
Uridine diphosphate-dependent glycosyltransferases (UGTs) catalyze the transfer of a diversity of sugars to several acceptor molecules and often exhibit distinct substrate specificity. Modulation of glycosyltransferases for increased catalytic activity and altered substrate or product specificity are the key manipulations for the biotechnological use of glycosyltransferases in various biosynthetic processes. Here, we have engineered the binding pocket of three previously characterized Vitis vinifera glycosyltransferases, UGT88F12, UGT72B27 and UGT92G6, by structure-guided in silico mutagenesis to facilitate the interactions of active site residues with flavonol glucosides and thus modify substrate specificity and activity. Site-directed mutagenesis at selected sites, followed with liquid chromatography-mass spectrometry based activity assays, exhibited that mutant UGTs were altered in product selectivity and activity as compared to the wild-type enzymes. Mutant UGTs produced larger amounts of flavonol di-monosaccharide glucosides, which imply that the mutations led to structural changes that increased the volume of the binding pocket to accommodate a larger substrate and to release larger products at ease. Mutants showed increased activity and modified product specificity. Thus, structure-based systematic mutations of the amino acid residues in the binding pocket can be explored for the generation of engineered UGTs for diverse biotechnological applications.
Keywords: flavonol; Glycosyltransferase; in silico analysis; Mutagenesis; selectivity

Phenylpropanoid-specific glycosyltransferases from mango and their potential role in defense - Vare, Tejas; Joshi, Rakesh; Liao, Jieren; Hoffmann, Thomas; Schwab, Wilfried; Giri, Ashok (Plant Physiology and Biochemistry, 2026)
Alphonso mango (Mangifera indica cv. Alphonso) is a cornerstone of India's fruit industry due to its distinct aroma and shelf-life characteristics. The uridine diphosphate-dependent glycosyltransferases (UGTs) play a crucial role in stabilising aroma and defense-related specialised metabolites in fruits. The present study explores the potential role of UGTs during mango ripening and Colletotrichum gloeosporioides infection. Gene expression analysis indicated that UGTs showed dynamic expression in skin and pulp during ripening. Phylogenetic analysis revealed substrate-driven divergence of UGTs, with MiUGT92A14 and MiUGT95B15 forming distinct clades associated with flavonoid glycosylation. Recombinant UGTs showed a higher preference for UDP-glucose, which is corroborated by the high accumulation of UDP-glucose during ripening. Furthermore, it was observed that MiUGT92A14 prefers phenolic acids as substrates, while MiGT95B15 shows flavonoid specificity. Spore germination assays demonstrated that both aglycones and their glycosylated derivatives suppressed early fungal morphogenesis, supporting a role for UGT-mediated glycosylation in maintaining defense-related metabolites in a bioactive yet non-toxic form during fruit ripening. Additionally, Colletotrichum gloeosporioides inhibition assays demonstrated that glycosylated products of selected UGTs exhibited equal or enhanced antifungal activity compared with their aglycone forms, indicating that glycosylation promotes the safe accumulation of antifungal compounds by reducing aglycone toxicity to the plant. These findings suggest that glycosylation of specific metabolites is a key for ripening process and to potentiate defence against fungal pathogen.
Keywords: Anthracnose; defense; Flavonoid; Glycoconjugates; Uridine diphosphate-dependent glycosyl-transferase